Three new species of the genus Macgregoromyia Alexander, with a key to world species (Diptera, Tipulidae) - Liu, Qifei; Yang, Ding (Zootaxa, 2011)
The following three new species of the genus Macgregoromyia Alexander from China are described: Macgregoromyia ternifoliusa sp. nov., M. flatusa sp. nov. and M. rectangularis sp. nov. A key to the world species of the genus Macgregoromyia is presented.